UPAYA MENUMBUHKAN PATRIOTISME DAN NASIONALISME MELALUI REVITALISASI MAKNA IDENTITAS NASIONAL DI KALANGAN GENERASI MUDA - Aristin, Rini (Aspirasi: Jurnal Ilmiah Administrasi Negara, 2017)
It has been 72 years since Indonesia proclaimed it self as an independent country. Indonesia should now be a developed country and free from all forms of colonization in accordance with the ideals of Pancasila and the 1945 Constitution and the founding fathers of the nation. However, the negative impacts of the modernization turn out to be a threat that is no less frightening than the colonial era in the period before independence first. The negative impact is felt by the younger generation who then grow into a generation that has no purpose and loss of sense of nationalism and patriotism. Through the revitalization of the meaning of national identity among the younger generation is expected the youth more love the country. Especially on the various characteristics possessed by the Indonesian nation in the form of national identity, covers fundamental identity, instrumental identity and natural identity.